Problem-solving disposition as a predictor of preservice elementary teachers’ problem-solving performance - Dangkulos, Theresa G.; Ibañez, Edwin D.; Pentang, Jupeth Toriano (Journal of Education and Learning (EduLearn), 2025)
Proficiency in solving mathematical problems is essential for preservice elementary teachers, as they will teach foundational math concepts and foster problem-solving abilities among young learners. However, many studies found low problem-solving performance among preservice teachers. In line with this, the present study examined how problem-solving disposition relates to the performance of preservice elementary teachers, conducted at a selected higher education institution in Nueva Ecija, Philippines, with 134 participants. The study utilized a mathematical problem-solving disposition and beliefs scale questionnaire and a problem-solving test scored using the identify, define, explore, act, and look (IDEAL) model. Results indicated an average problem-solving disposition and high problem-solving performance among preservice teachers. Linear regression analysis showed that overall problem-solving disposition is a predictor of performance. Further, stepwise regression analysis revealed that two disposition parameters, mathematical mindset (β = 2.413, p 0.01) and community of practice (β = 1.866, p 0.01), significantly predicted problem-solving performance. These findings show the significance of developing a problem-solving disposition, mindset, and learning communities to improve future teachers’ problem-solving ability by providing more learning opportunities, interdisciplinary problems, and social engagements.